If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4x+35=-7x-8(1+5x)
We move all terms to the left:
-4x+35-(-7x-8(1+5x))=0
We add all the numbers together, and all the variables
-4x-(-7x-8(5x+1))+35=0
We calculate terms in parentheses: -(-7x-8(5x+1)), so:We get rid of parentheses
-7x-8(5x+1)
We multiply parentheses
-7x-40x-8
We add all the numbers together, and all the variables
-47x-8
Back to the equation:
-(-47x-8)
-4x+47x+8+35=0
We add all the numbers together, and all the variables
43x+43=0
We move all terms containing x to the left, all other terms to the right
43x=-43
x=-43/43
x=-1
| 3u8=4 | | 3(2x+6)8x=46 | | (4)=2(x-2)+5 | | 8m+6m−12=72 | | 5x=3x-48 | | a=2.3-7 | | 8+10=-3(7x-6) | | 5/19=c5/7 | | 5x+20=2x-7 | | 4(x-1)+4x−1=19 | | 2p-16=2 | | /3x+2x=12-x | | -2+n=-2(1+n) | | -8+3h=2 | | |5n|+8=38 | | 5z+12+4z-3=2z+6 | | 7=11+n | | -14-9x=22x= | | 5x+2=2(8-x) | | .3x-4=2x-35 | | 11m+9=19m-19-20 | | 8-7k=-9k | | –7y+1=8 | | 5(3-2x)=4x=15-14x | | -6x-33=-5(x+5) | | -18+36=-3(x+7) | | 5(x+2)-7=3x+5 | | 6=r/2+3 | | 110=13+3(4h−6) | | (23x1.8)+32=F | | 0=x/2+7 | | 2x+6=13×2 |